Effect of relative age in men`s ice hockey: the analysis of playing positions, hand dominance, and the level of basic anthropometric characteristics at the Ice Hockey World Championships 2017 - Bozdech, M.; Agricola, A.; Zhanel, J. (Journal of Physical Education and Sport, 2019)
The issue of Relative Age Effect (RAE), i.e. the influence of birthdate on performance, has been studied in sports over the last decades. Benefits in terms of morphological, psychological andphysiological characteristics resulting from earlier birthdates for athletes in the same age category often cause that, especially in junior categories, these relatively older individuals are perceived as sportingly talented. The influence of RAE in ice hockey has been proven in different categories, but only a few studies have been devoted to the RAE influence in national teams. The aim of this research was to analyse the RAE in players (n=402; Age M ±SD=27.0±4.16 SD) at the 2017 Ice Hockey World Championships (IHWC) in the context of playing positions, hand dominance and the level of basic anthropometric characteristics. Research data were obtained from the publicly available sources and analysed with the methods of descriptive and inferential statistics (relative and absolute frequency, chi-square test, odds ratio test, Cohen`s w and Hedge`s g). The results showed that from the point of view of effect size (ES), the influence of RAE can be considered small for both the entire researched group of2017 IHWC players and for the individual playing positions. From the point of view of statistical significance, the influence of RAE cannot be dismissed for the entire group of players and also for the group of right-handed forwards. Also the effect size (ES)of RAE in the context of hand dominance is small, with virtually small differences in body height and weight found between Q1 and Q4 players in almost all players. Summarily, it can be stated that only a small, resp. partial degree of RAE in national teams at the 2017 IHWC was demonstrated, also in the context of playing positions, hand dominance and the level of basic anthropometric characteristics.